Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Energy-sector footprints, subsequent disturbances and footprint reclamation determine the direction and rate of landbird community trajectories in boreal forests - Tharindu Kalukapuge; Christine M. Godwin; Kenneth R. Foster; James F. Saracco; Erin Bayne (Journal of Environmental Management, 2026)

Stocks and shocks: Assessing the relative roles of public and private inventories in buffering rice price volatility in the Philippines - Bernhard Dalheimer; Kenneth Foster; Gerald Shively; Valerien O. Pede; Dela-Dem Doe Fiankor; Jacob Ricker-Gilbert; Pratibha Bist (Food Policy, 2026)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Exposure to radiofrequency electromagnetic fields and IARC carcinogen assessment: Risk of Bias preliminary literature assessment for 10 key characteristics of human carcinogens - Myrtill Simkó; Michael H. Repacholi; Kenneth R. Foster; Mats-Olof Mattsson; Rodney J. Croft; Maria Rosaria Scarfi; Vijayalaxmi (Mutation Research - Reviews in Mutation Research, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Tetracycline and Oxacillin Act Synergistically on Biofilms and Display Increased Efficacy In Vivo Against Staphylococcus aureus - Amy K. Tooke; Rebecca E. Hodges; Josie F. Pyrah; Kenneth W. Bayles; Stephen A. Renshaw; Simon J. Foster (Current Microbiology, 2024)
Oxacillin (bactericidal) and tetracycline (bacteriostatic) are clinically relevant antibiotics that are routinely prescribed to treat Staphylococcus aureus infections but not conventionally used in combination. There is an urgent need for treatment regimens that can act upon biofilms during infection, associated with chronic infections on indwelling devices, as well as acute planktonic (systemic) infection. Here we show that in an in vitro model oxacillin and tetracycline act synergistically against S. aureus UAMS-1 biofilms, reducing the concentration of both antibiotics necessary to eradicate an established biofilm. Using an in vivo zebrafish larval infection model with S. aureus NewHG, they display improved bacterial clearance compared to each drug alone and can counteract a loss of host phagocytes, an important innate defence against S. aureus . In these cases, the bacteriostatic nature of tetracycline enhances rather than dampens the bactericidal action of oxacillin, although an exact mechanism remains to be elucidated. We suggest a dual therapy could be of clinical use against biofilm-forming S. aureus and has a potential use in patients with a compromised immune system.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Effects of alternative hermetic bag storage on fermented and dried cocoa bean (Theobroma cacao L.) - Kenneth A. Foster; Lina M. Suarez-Guzman; Diana C. Meza-Sepulveda; Dieudonne Baributsa; Carlos A. Zurita (Journal of Stored Products Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Environmental engagement in troubled times: a manifesto - James D. Proctor; Jennifer Bernstein; Philip Brick; Emma Brush; Susan Caplow; Kenneth Foster (Journal of Environmental Studies and Sciences, 2018)

Energy conserving thermoregulatory patterns and lower disease severity in a bat resistant to the impacts of white-nose syndrome - Marianne S. Moore; Kenneth A. Field; Melissa J. Behr; Gregory G. Turner; Morgan E. Furze; Daniel W. F. Stern; Paul R. Allegra; Sarah A. Bouboulis; Chelsey D. Musante; Megan E. Vodzak; Matthew E. Biron; Melissa B. Meierhofer; et al. (Journal of Comparative Physiology B, 2018)

Sea Turtle Bycatch Mitigation in U.S. Longline Fisheries - Yonat Swimmer; Alexis Gutierrez; Keith Bigelow; Caren Barceló; Barbara Schroeder; Kenneth Keene; Keith Shattenkirk; Daniel G. Foster (Frontiers in Marine Science, 2017)

Isolation and characterization of eight novel microsatellite loci in endangered Wyoming toad, Bufo baxteri - Renee M. Martin; Connie L. Keeler-Foster; Kenneth G. Boykin; Gerard Zegers; Wade D. Wilson (Conservation Genetics Resources, 2012)

Impacts of Oyster Reef Restoration on Primary Productivity and Nutrient Dynamics in Tidal Creeks of the North Central Gulf of Mexico - Rochelle Plutchak; Kelly Major; Just Cebrian; C. Drew Foster; Mary-Elizabeth C. Miller; Andrea Anton; Kate L. Sheehan; Kenneth L. Heck; Sean P. Powers (Estuaries and Coasts, 2010)

Roles of cyclic AMP in regulation of phototaxis in Chlamydomonas reinhardtii - Maskiet Boonyareth; Jureepan Saranak; Darawan Pinthong; Yupin Sanvarinda; Kenneth W. Foster (Biologia, 2009)

The impact of Hurricane Ivan on the primary productivity and metabolism of marsh tidal creeks in the NorthCentral Gulf of Mexico - Just Cebrian; C. Drew Foster; Rochelle Plutchak; Kate L. Sheehan; Mary-Elizabeth C. Miller; Andrea Anton; Kelly Major; Kenneth L. Heck; Sean P. Powers (Aquatic Ecology, 2008)

Nitrogen fixation by unicellular diazotrophic cyanobacteria in the temperate oligotrophic North Pacific Ocean - Joseph A. Needoba; Rachel A. Foster; Carole Sakamoto; Jonathan P. Zehr; Kenneth S. Johnson (Limnology and Oceanography, 2007)
N 2 fixation has been understudied in marine environments outside of the subtropical and tropical oceans and where water temperatures are typically below 20‐25°C. We identified nifH phylotypes and measured N 2 fixation rates under ambient conditions (maximum of 19°C) in water collected 750 km off the coast of California in oligotrophic waters of the North Pacific Ocean (34°N, 129°W). Near‐surface N 2 fixation rates averaged 0.25 ± 0.05 nmol N L −1 d −1 for 24 incubation bottles. Despite low ambient concentrations of iron ( −1 ) and phosphorus ( −1 ), N 2 fixation rates were unaffected by iron and phosphorus amendments. Using reverse transcription‐quantitative polymerase chain reaction (RT‐QPCR) methodology, we estimated transcript abundance and patterns of expression for several unicellular diazotrophs, including the group A phylotype, which showed the highest daily mRNA abundances. The N 2 ‐fixing assemblage extended to 60‐80 m depth, well below the seasonal thermocline (40 m). The calculated areal N 2 fixation rate (15 µmol N m −2 d −1 ) was small compared with estimates from other regions of the Pacific; however, the estimated fixation rate was similar to other published results, suggesting that processes other than cellular growth rate may determine the abundance of unicellular diazotrophs. Despite the low N 2 fixation rates, the new nitrogen added to the euphotic zone by N 2 fixation could account for at least 10% of new production during the study period.

A Screening Test for the Determination of Ethylene Sensitivity - Daniel J. Archambault; Xiaomei Li; Kenneth R. Foster; T. R. Jack (Environmental Monitoring and Assessment, 2006)

Increased extracellular glutamate evoked by 1-Methyl-4-phenylpyridinium (MPP+) in the rat striatum is not essential for dopaminergic neurotoxicity and is not derived from released glutathione - Steven B. Foster; Haiwang Tang; Kenneth E. Miller; Glenn Dryhurst (Neurotoxicity Research, 2005)

Growth rate and potential climate record from a rhodolith using 14C accelerator mass spectrometry - Brian R. Frantz; Michaele Kashgarian; Kenneth H. Coale; Michael S. Foster (Limnology and Oceanography, 2000)
Rhodoliths, free‐living calcareous red algae, create large and diverse habitats worldwide. Although these plants are abundant and ecologically important, little is known about their growth rate. We determined the growth rate for an individual rhodolith, Lithothamnium crassiusculum , from the southern Gulf of California through 14 C analysis using accelerator mass spectrometry (AMS) to be 0.6 mm yr −1 . This growth rate suggests large L. crassiusculum , which have been found with radii in excess of 6 cm, may live over 100 yr. Declines in the Δ 14 C record associated with the large El Niño events of 1957, 1982, and 1992 indicate 14 C analysis may lead to identification of important climate events in the more distant past. The ability to determine changes in past ocean circulation related to changes in past climatic conditions through AMS 14 C analysis of rhodoliths would increase the geographic range of available climate records from the tropical oceans to the entire global ocean and potentially allow for the determination of past climate conditions from rhodoliths in fossil beds.

Light induces accumulation of isocitrate lyase mRNA in a carotenoid-deficient mutant of Chlamydomonas reinhardtii - Sevastiani Petridou; Kenneth Foster; Karen Kindle (Plant Molecular Biology, 1997)